Air conditioning system maintenance and repair training for youth of Karang Taruna - Wanda Afnison; Primawati Primawati; Wagino Wagino; Nuzul Hidayat; Dieter Rahmadiawan (Universitas Muhammadiyah Magelang, 2023)
This work reports on social service activities at the Department of Automotive Engineering, Faculty of Engineering, Universitas Negeri Padang. This activity is targeted at out-of-school youth in Karang Taruna. The service is carried out in order to increase knowledge and skills in repairing and maintaining the Air Conditioner (AC) system in cars. Through this program, it is hoped that new experiences and knowledge can benefit the people of Karang Taruna. This program is carried out by delivering the basic theory of the car air conditioner working system. The activity is carried out using an AC system trainer. The participants were given an understanding of the methodology, the system of the refrigerants, and how to maintenance or repair the car's air conditioning system. The success rate of this activity is evidenced by the results of the post-test, in which an increment in the average score of 14.4 points.